Moti: Interactive rehabilitation for children between 2 and 6 years old who attend occupational therapy (2017)
Occupational therapy is a person-centered profession concerned with promoting a balanced range of occupations to enhance health and wellbeing. Small children and toddlers may experience disruption to their occupations due to injury, illness or disability, family circumstances, or at times of transition. In Colombia, the field of occupational therapists increased around 250% between 1985 and 2000 (Trujillo, 2013), and according to Doctor Paola Araque (who is a therapist of one of the most recognized occupational centers in Bogotá called Sensory kids), there are around 20 to 30 new children who need occupational therapy every three months in each one of the centers in Bogota. Occupational therapists spend time finding out about the child?s and family?s typical daily life and what they want, need or are expected to do. They work together with the child, family and other key people to evaluate what helps or hinders their involvement in daily life roles. Moti wants to be part of this, and together, possible solutions will be developed, such as exploring alternative ways of doing things or making changes to the environment to support participation. We observed a need and an opportunity in the fact that nowadays it is very hard to maintain the child?s attention to perform the therapies, and moreover, in the fact that these take a long time because children only take one hour daily to do therapies at the therapy centers. Moti wants to be in the homes of the cognitive stable children between two and six years old who do occupational therapy so that they can continue with their process in their home in a fun way, then we can help the children to strengthen their independence, through various occupations, but including the missing part nowadays, which is the motivational factor in the occupational therapy, so the children will be motivated to increase the frequency of their therapies